Trainer Atmega32 Sebagai Media Pelatihan Mikrokontroler Dan Arduino - I Gusti Made Ngurah Desnanjaya; Ida Bagus Ary Indra Iswara (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2018)
The microcontroller is one of the necessary parts of a computer system. In a simple microcontroller will produce a specific output based on the input received and the program given. The microcontroller as semiconductor technology its presence greatly assist the development of electronics world. With a functional architecture but contains a lot of transistor content is integrated, thus supporting the creation of a more portable electronic circuit. One effort made to graduate Computer Systems courses can compete in the world of work is to provide more practice. Therefore it takes the media trainer microcontroller training to facilitate practical activities. Through this research, hope can realize a media trainer microcontroller training that can do the instructions given. That is, the most critical part of a computerized system is the program itself created by a programmer.